Energy absorption characteristics of honeycomb-filled tube under impact loading [electronic resource] - Yong, Wei Lun, 1989-, author (2013)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2013